Lunns and Bunns - Raffael, Michael (Petits Propos Culinaires, 2007)
This piece come from Michael Raffael’s new book Bath Curiosities (Birlinn, £9.99), essays about the history of Bath. It is not invariably food-centred – indeed there is a chapter both on my great-uncle Sidney Horstmann and the location of my first paying work, Harbutt’s Plasticine – however, on the food front there are chapters on fizzy pop and soda water, the Bath bun, Bath markets and Bath Olivers. It’s full of fun and proper curiosities. I am grateful to both publisher and author for permission to print this piece.